The conjugacy of the vestibulo-ocular reflex evoked by single labyrinth stimulation in awake monkeys - Tang, Xuehui (2010)
It is well known that the vestibulo-ocular reflex (VOR) is conjugate when measured in the dark with minimal vergence. But the neural basis of the VOR conjugacy remains to be identified. In the present study, we measured the VOR conjugacy during single labyrinth stimulation to examine whether the VOR conjugacy depends on reciprocal stimulation of the two labyrinths. There are conflicting views on this issue. First, since the vestibular signals carried by the ascending tract of Deiters' are distributed exclusively to the motoneurons of the ipsilateral eye, the neural innervations after single labyrinth stimulation are not symmetrical for the two eyes. Thus, single labyrinth stimulation may generate disjunctive VOR responses. Second, the only published study on this issue was an electrooculography (EOG) study that reported disjunctive VOR responses during unilateral caloric irrigation (Wolfe in Ann Otol 88:79–85, 1979). Third, the VOR during unilateral caloric stimulation performed in clinical vestibular tests is routinely perceived to be conjugate. To resolve these conflicting views, the present study examined the VOR conjugacy during single labyrinth stimulation by recording binocular eye position signals in awake monkeys with a search coil technique. In contradiction to the previous EOG study and the prediction based on the asymmetry of the unilateral brainstem VOR circuits, we found that the VOR during unilateral caloric irrigation was conjugate over a wide range of conditions. We conclude that the net neural innervations received by the two eyes are symmetrical after single labyrinth stimulation, despite the apparent asymmetry in the unilateral VOR pathways. A novel role for the ascending tract of Deiters' in the VOR conjugacy is proposed.